A disorder clinically resembling cystic fibrosis caused by biallelic variants in the AGR2 gene. Issue 10 (24th December 2021) - Bertoli-Avella, Aida; Hotakainen, Ronja; Al Shehhi, Maryam; Urzi, Alice; Pareira, Catarina; Marais, Anett; Al Shidhani, Khoula; Aloraimi, Sumaya; Morales-Torres, Galina; Fisher, Steffen; Demuth, Laura; Moteleb Selim, Laila Abdel; et al.
Abstract : Purpose: We sought to describe a disorder clinically mimicking cystic fibrosis (CF) and to elucidate its genetic cause. Methods: Exome/genome sequencing and human phenotype ontology data of nearly 40 000 patients from our Bio/Databank were analysed. RNA sequencing of samples from the nasal mucosa from patients, carriers and controls followed by transcriptome analysis was performed. Results: We identified 13 patients from 9 families with a CF-like phenotype consisting of recurrent lower respiratory infections (13/13), failure to thrive (13/13) and chronic diarrhoea (8/13), with high morbidity and mortality. All patients had biallelic variants in AGR2, (1) two splice-site variants, (2) gene deletion and (3) three missense variants. We confirmed aberrant AGR2 transcripts caused by an intronic variant and complete absence of AGR2 transcripts caused by the large gene deletion, resulting in loss of function (LoF). Furthermore, transcriptome analysis identified significant downregulation of components of the mucociliary machinery (intraciliary transport, cilium organisation), as well as upregulation of immune processes. Conclusion: We describe a previously unrecognised autosomal recessive disorder caused by AGR2 variants. AGR2 -related disease should be considered as a differential diagnosis in patients presenting a CF-like phenotype. This has implications for the molecular diagnosis and management of these patients. AGR2 LoF is likely the disease mechanism, with consequent impairment of the mucociliary defence machinery. Future studies should aim to establish a better understanding of the disease pathophysiology and to identify potential drug targets.